Advances in photocatalytic research on decarboxylative trifluoromethylation of trifluoroacetic acid and derivatives - Tan, Fang-Fang; Li, Zhan-Chao (Frontiers in Chemistry, 2025)
Trifluoromethylation stands as a pivotal technology in modern synthetic chemistry, playing an indispensable role in drug design, functional material development, and agrochemical innovation. With the growing emphasis on green chemistry principles, the pursuit of environmentally benign trifluoromethylation strategies has emerged as a critical research frontier. Trifluoroacetic acid (TFA), characterized by its cost-effectiveness, stability, and low toxicity, has become a promising alternative to conventional trifluoromethylation reagents. This review systematically summarizes advancements in photocatalytic decarboxylative trifluoromethylation using TFA and its derivatives over the past decade, focusing on three key activation mechanisms: single-electron transfer (SET), electron donor-acceptor (EDA) complex-mediated pathways, and ligand-to-metal charge transfer (LMCT). This paradigm shift is driven by the intrinsic limitations of conventional thermal decarboxylation, particularly its reliance on harsh conditions and significant environmental burdens. In contrast, photocatalytic strategies enable efficient C–CF3 bond construction under mild conditions, offering a modular platform for synthesizing fluorinated functional molecules. Strategic research priorities should focus on overcoming fundamental challenges, including but not limited to optimizing photosensitizer catalytic efficiency, establishing regioselective manipulation strategies, and engineering multicomponent tandem reaction systems to achieve trifluoromethylation methodologies under mild conditions. Furthermore, the integration of mechanistic investigations with artificial intelligence-driven reaction prediction will accelerate the advancement of precision trifluoromethylation technologies. This progress is anticipated to provide sustainable synthetic solutions for next-generation fluorinated pharmaceuticals and advanced functional materials, effectively bridging the innovation gap between academic research and industrial implementation.